2021
DOI: 10.7554/elife.61700
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 adrenergic receptor antagonists to prevent hyperinflammation and death from lower respiratory tract infection

Abstract: In severe viral pneumonia, including Coronavirus disease 2019 (COVID-19), the viral replication phase is often followed by hyperinflammation, which can lead to acute respiratory distress syndrome, multi-organ failure, and death. We previously demonstrated that alpha-1 adrenergic receptor (⍺1-AR) antagonists can prevent hyperinflammation and death in mice. Here, we conducted retrospective analyses in two cohorts of patients with acute respiratory distress (ARD, n = 18,547) and three cohorts with pneumonia (n = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 43 publications
(51 reference statements)
1
35
0
Order By: Relevance
“…Additional work using transgenic mouse modeling and dedicated in vitro studies will be required to more fully explore this connect, as will larger prospective studies of patients with IPF. Nevertheless, these findings carry significance for the relatively rare condition of IPF as well as for numerous cross organ conditions of adrenergic overactivation, inflammatory remodeling and mtDNA such as non-alcoholic hepatic steatosis (33, 49), cardiac fibrosis (50), obesity (51, 52), ARDS (43, 53), and COVID-19 (46, 54), and suggest a convergent mechanism for divergent disease states.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Additional work using transgenic mouse modeling and dedicated in vitro studies will be required to more fully explore this connect, as will larger prospective studies of patients with IPF. Nevertheless, these findings carry significance for the relatively rare condition of IPF as well as for numerous cross organ conditions of adrenergic overactivation, inflammatory remodeling and mtDNA such as non-alcoholic hepatic steatosis (33, 49), cardiac fibrosis (50), obesity (51, 52), ARDS (43, 53), and COVID-19 (46, 54), and suggest a convergent mechanism for divergent disease states.…”
Section: Discussionmentioning
confidence: 93%
“…α1 adrenoreceptor antagonism is emerging as a potential treatment for diseases characterized by inflammatory remodeling such as ARDS and COVID-19 (11, 42, 43) and we have previously shown that IPF patients taking these agents experienced preserved lung function and improved survival (11). In an attempt to link these clinical observations to the basic science studies shown above, we evaluated the relationship between plasma mtDNA concentrations – a reproducible biomarker of both fibroblast activation and mortality in the IPF disease state (21, 44, 45) – and α1 adrenoreceptor antagonism t in a longitudinal cohort of IPF patients followed at the Yale ILD Center of Excellence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although nicotine is suggested to alleviate immune dysregulation and inhibit cytokine storm, inhalation of nicotine from tobacco could increase the risk of SARS-CoV-2 infection due to upregulation of ACE2. Two population-based clinical cohort studies revealed and analyzed that treatment of influenza, pneumonia, or ARDS patients with α1-adrenergic blockers could reduce 30-day mortality, risk of intensive care unit admission, mechanical ventilation, and death ( Koenecke et al, 2021 ; Thomsen et al, 2021 ). In future studies, research and development of therapeutic strategies or drugs that can inhibit and counterbalance inflammatory cytokine secretion through adrenergic and cholinergic pathways are considered that may play an important role in helping us bring some enlightenment for treating COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Here we introduce a potential COVID-19 pharmaceutical treatment to discuss the 10 rules more concretely. Prior work indicates that certain alpha-1 adrenergic receptor antagonists (alpha blockers) disrupt cytokine storm syndromes, a pathological hyperinflammatory response associated with respiratory infection and other diseases (Staedtke et al, 2018;Koenecke et al, 2021;Thomsen et al, 2021). Subsequently, others determined that hyperinflammation is implicated in morbidity and mortality in COVID-19 patients (Mehta et al, 2020;Li et al, 2021).…”
Section: Covid-19 Studymentioning
confidence: 99%